PENGARUH KECERDASAN BUATAN TERHADAP PENGEMBANGAN KOGNITIF DALAM PENDIDIKAN - Loso Judijanto; Rafika Nisa; M. Amin Fatulloh; Al-Amin (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
The development of technology with the emergence of AI as a potentially transformative tool in the learning process. The research method conducted in this study uses the literature method. The results show that AI has the potential to improve learning effectiveness and encourage beter cognitive development. However, it also highlights potential challenges, including the risk of over-reliance on technology and the importance of maintaining human interaction in the educational process. Thus, while AI offers significant opportunities to enhance cognitive development in education, a balanced and ethical approach to its implementation is required